Identification of the complete mitochondrial genome of the pacific white shrimp Litopenaeus vannamei (Decapoda: Penaeidae). (1st November 2016) - Liu, Qiu-Ning; Chai, Xin-Yue; Jiang, Sen-Hao; Zhou, Chun-Lin; Xuan, Fu-Jun; Zhang, Dai-Zhen; Tang, Bo-Ping
Abstract: The complete mitochondrial genome (mitogenome) of Litopenaeus vannamei was determined to be 15 989 bp in size, it contains 22 tRNA genes, 13 protein-coding genes (PCGs), two rRNA genes and a D-loop region. The nucleotide composition was biased toward A + T nucleotides (67.8%) and the AT skew of this mitogenome was slightly negative (−0.025). All tRNA genes displayed a typical clover-leaf structure, except for trnS1 (AGN). Thirteen PCGs were initiated by ATN codons, except for cox1 gene which was initiated by ACG. Four of the 13 PCGs had the incomplete termination codon by T. The rrnL was 1371 bp and the rrnS was 853 bp, and the AT content of the combined rRNA genes was 70.9%. The D-loop region of the mitogenome was 985 bp in length and the A + T content was 82.7%, and no tandem repeat was found in this region. Phylogenetic analysis showed that the placement of L. vannamei was within the Penaeidae.